2017
DOI: 10.1080/07317115.2017.1398799
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Awareness Campaign in the Latino Community: A Novel Community Engagement Pilot Training Program withPromotoras

Abstract: In order to get Latinos to seek early detection, we need to first educate them about dementia, win trust, and encourage treatment-seeking. Early intervention, diagnosis, and prevention will benefit from educational campaigns using the CBPR model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Dementia awareness campaigns have focused on topics as improving recognition of dementia, 25 dementia care, 26 decreasing public stigma 27 28 and few on dementia risk reduction. 29 30 An Australian study using an informative website on dementia risk reduction resulted in increased knowledge and motivation to engage in relevant health behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia awareness campaigns have focused on topics as improving recognition of dementia, 25 dementia care, 26 decreasing public stigma 27 28 and few on dementia risk reduction. 29 30 An Australian study using an informative website on dementia risk reduction resulted in increased knowledge and motivation to engage in relevant health behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies employed between 19 and 25 CHWs and the other five studies involved less than 10 CHWs for community interventions. The CHWs were predominantly female in the studies that reported sex with percentages of 83.30%, 91.67%, and 95% in Han et al (2013), Boughtwood et al (2013), and Askari et al (2018, respectively, and 100% in Shaji et al (2002), Ramos-Cerqueira et al (2005), and Jacob et al (2007). The majority of the CHWs had secondary school education to college degrees (Han et al, 2013;Jacob et al, 2007;Kvalsund et al, 2009;Ramos-Cerqueira et al, 2005;Robbins et al, 2011).…”
Section: Characteristics Of Chwsmentioning
confidence: 93%
“…One additional article was excluded with the help of third reviewer due to insufficient details about methodology. Finally, 10 articles were selected to be included in this review (Askari et al, 2018;Boughtwood et al, 2013;Han et al, 2013;Jacob et al, 2007;Kvalsund et al, 2009;Litzelman et al, 2017;Ramos-Cerqueira et al, 2005;Robbins et al, 2011;Shaji et al, 2002;Souder & Terry, 2009). No additional articles were found meeting the eligibility criteria in the forward and backward search.…”
Section: Study Selectionmentioning
confidence: 99%
“…However, the exhibited symptoms of concomitant depression and dementia are often perceived as misbehavior by caregivers or relatives when lacking the relevant information on these two conditions, which could further lead to behavioral and functional consequences and the risk of adverse outcomes, including heightened caregiver burden . The misperception and ignorance regarding depression in dementia patients could be especially true in the developing world, where public awareness of dementia is relatively low . Therefore, investigating the information about the association between depression of people with dementia and caregiver burden could be useful for interventions for dementia caregiver burden in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The misperception and ignorance regarding depression in dementia patients could be especially true in the developing world, where public awareness of dementia is relatively low. 15 Therefore, investigating the information about the association between depression of people with dementia and caregiver burden could be useful for interventions for dementia caregiver burden in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%